CAUDAMMINA GUTTA, A NEW SPECIES OF HORMOSINELLIDAE (FORAMINIFERIDA) FROM THE RUPELIAN OF SICILY (ITALY) - ANDREA BENEDETTI; JOHANNES PIGNATTI (Rivista Italiana di Paleontologia e Stratigrafia, 2009)
A new species of agglutinated foraminifer, Caudammina gutta n. sp., is described from Lower Oligocene (upper Rupelian) strata of the Caltavuturo Formation near Portella Colla in the Madonie Mts. (northern Sicily). The new species comes from assemblages rich in deep-water agglutinated foraminifers (DWAF). Biometrical data based on two populations of the new species are compared with the species currently referred to the genus Caudammina, as yet known from the Tithonian to the Middle Eocene. C. gutta n. sp. has a large-sized pyriform test and is the end-member of a Cretaceous-Paleogene lineage which is interpreted as an example of size increase in time conforming to Cope’s rule.